Use of Ansys Workbench Computational Tool Applied to Teaching in Engineering Course (International Journal of Geoscience, Engineering and Technology, 2022)
The statics of rigid bodies are analyzed and often misunderstood in engineering courses. With the advancement of technology, the use of computational tools can help the “teaching-learning” process and has become increasingly common, promoting the understanding of curriculum components, such as the resolution of theoretical activities and practical exercises. For the development of this work, the classic flat truss exercise was used, taken as the theoretical definition of the problem. Through this definition, we proceeded with a step of numerical modeling using a computational tool ANSYS WORKBENCH Student Version. The results were satisfactory considering the comparison between the calculated (theory) and numerical (CFD) results, corrected for a relative error in the range of 0.01% to 0.39%. In this sense, a numerical simulation is performed efficiently, and the ANSYS computational tool can be proposed in the teaching process of engineering courses.